Stimuli-Responsive Electronic Reconfiguration in Benzo(ghi)perylene-TCNQ Donor–Acceptor Crystalline Networks - Gubanov, Kirill; Reva, Yana; Bo, Yifan; Hampel, Frank; Späth, Andreas; Beinik, Igor ; 0000-0002-4944-1398; Thånell, Karina; Brzhezinskaya, Maria; Furxhiu, Stevie; Uhlein, Timo; Ng, Siowwoon; Guldi, Dirk M.; et al. (Chemistry of Materials, 2025)
Template-assisted crystal engineering provides a powerful strategy for constructing ordered networks tailored to organic electronic applications. We introduce a solution-based strategy to fabricate crystalline needle-like arrays of charge-transfer complexes (CTCs) between electron-donating benzo(ghi)perylene (BP) and electron-accepting TCNQ. Well-defined square-crystals of BP polymorphs were employed as templates for the spatially controlled anisotropic growth of CTC needle-like arrays. By tuning concentration and deposition rates, we modulated BP crystal dimensions and hence controlled the growth of needle-networks mimicking the template spatial scale. In solution, these free-standing flexible meshes were detached from the BPs and redeposited onto variable substrates, while the BP templates remain undissolved, enabling repeated fabrication cycles. CTC formation induces an electronic redistribution with thermally reversible modulation of characteristic electronic states. Such transformation modifies the BP luminescence character: while bare BP exhibits a strong green emission, it is quenched in the presence of TCNQ and replaced by a weaker blueish CTC emission, establishing a charge-transfer-mediated photonic response. Our study provides a combination of crystal engineering with microspectroscopic insights offering a highly sensitive handle for elucidating charge redistribution and modulation of electronic states in CTC upon external stimuli.